2022
DOI: 10.1186/s13031-022-00465-x
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study to assess the impact of COVID-19 on maternal, newborn, child health and nutrition in fragile and conflict-affected settings

Abstract: Background The impacts of COVID-19 are unprecedented globally. The pandemic is reversing decades of progress in maternal, newborn, child health and nutrition (MNCHN), especially fragile and conflict-affected settings (FCAS) whose populations were already facing challenges in accessing basic health and nutrition services. This study aimed to investigate the collateral impact of COVID-19 on funding, services and MNCHN outcomes in FCAS, as well as adaptations used in the field to continue activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(65 citation statements)
references
References 88 publications
0
63
0
Order By: Relevance
“…Rodo et al. also reported that the COVID-19 pandemic might affect the maternal, newborn, and child health and nutrition in fragile and conflict-affected settings through literature review ( 26 ). A recent study by Ghesquière et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rodo et al. also reported that the COVID-19 pandemic might affect the maternal, newborn, and child health and nutrition in fragile and conflict-affected settings through literature review ( 26 ). A recent study by Ghesquière et al.…”
Section: Discussionmentioning
confidence: 99%
“…WHO estimates 500,000 more deaths from TB in 2020 than would otherwise be expected ( Roberts, 2021 ). WHO and UNICEF have reported the largest decline in childhood vaccinations in 30 years ( WHO, 2022c ) and reduced funding for maternal child health services and family planning has disrupted supply and demand of maternal child health interventions and decreased contraceptive access and use ( Rodo et al, 2022 ; Catterson, 2021 ). While these impacts are not directly attributable to inequitable access to products to address the pandemic, delays in COVID-19 vaccination in LMICs may have exacerbated the effects of the pandemic on other health programs.…”
Section: Resultsmentioning
confidence: 99%
“…Disruptions in SRH service provision were widely reported 26 36 38 39 45 63 64. Reduced facility opening hours were reported in Makana Refugee Camp (Rwanda), Myanmar, North-East Nigeria and sub-Saharan Africa 38 42 45 62.…”
Section: Resultsmentioning
confidence: 99%